1999
DOI: 10.1002/(sici)1097-458x(199911)37:11<814::aid-mrc558>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of 3′-S-PO3-linked ribo- and deoxyribodinucleoside monophosphates

Abstract: The conformations of two phosphodiester‐linked dinucleotides and their analogues containing a 3′‐S‐phosphorothiolate linkage were investigated using 1H NMR spectroscopy. The phosphorus decoupled 1H NMR spectrum of each compound was simulated and values for the vicinal proton–proton coupling constants of the sugar ring hydrogens abstracted at several different temperatures, for use in full conformational analyses. The UV absorbance temperature profiles of the dimers were also analysed. It was found that in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…as in 1), hydrogen bonding, anomeric effects, gauche effects etc. [24,25] Other possible dynamic exchange equilibria could include dimerisation, either through intermolecular hydrogen bonding [26] or base stacking, [25,26] though the former is unlikely given the polarity of the solvent used here, and although speculative, the latter would nevertheless show markedly concentration-and temperature-dependent spectra (which was indeed the case for some samples, e.g. 5).…”
Section: H Chemical Shifts and Inmentioning
confidence: 79%
See 1 more Smart Citation
“…as in 1), hydrogen bonding, anomeric effects, gauche effects etc. [24,25] Other possible dynamic exchange equilibria could include dimerisation, either through intermolecular hydrogen bonding [26] or base stacking, [25,26] though the former is unlikely given the polarity of the solvent used here, and although speculative, the latter would nevertheless show markedly concentration-and temperature-dependent spectra (which was indeed the case for some samples, e.g. 5).…”
Section: H Chemical Shifts and Inmentioning
confidence: 79%
“…The two conformers of 1 also showed clear changes in the position of the north/south ring conformational equilibrium [24] of the sugar moiety (this conformational change is known to be fast on the NMR time scale [24,25] ) as evidenced by the magnitude of the proton vicinal coupling constants [25] Ðand indeed this is also expected to occur in concert with a syn and anti interconversion. [24] In contrast to expectations, though, [24] it is the syn conformer for which the north/south ring conformational equilibrium is more biased towards the north conformer (60 %, vs. 50 % for the anti conformer).…”
Section: H Chemical Shifts and Inmentioning
confidence: 93%
“…In simulating the spectra we followed our previous methodology. 12 In some instances sugar proton resonances overlapped with resonances from residual protons of the deuterated solvent or protons of the other sugar ring and thus precluded complete spectral simulation. The final results of the simulations are shown in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…20 In using this program the methodology we used previously has been followed here. 12 The results of a pseudorotational analysis for the four dinucleotides, in the three solvents, are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…It also has been observed that the deoxyribose pucker of the 3 -S-phosphorothiolate actually populates the north conformation to a greater extent than natural RNA. [4] For these 710 J. W. Gaynor et al reasons, it is expected that integration of the 3 -S-phosphorothiolate linkage into RNA will enhance duplex stability of a modified RNA strand to its complement.…”
Section: Introductionmentioning
confidence: 99%